Akuntabilitas Pada Pengelolaan Anggaran Kelurahan Di Kelurahan Harjasari Bogor - Dian Widyantini (CV. KAMPUSA AKADEMIK PUBLISING, 2024)
This research was conducted to determine the accountability of village budget management through the planning, implementation, and accountability stages in Harjasari Village, South Bogor District, Bogor City. The research method used is descriptive qualitative. Research data in the form of primary and secondary data, including the results of interviews and supporting data on village budget management. Data analysis techniques by reviewing the data collected and analyzing to then draw conclusions. The presentation of financial reports and budget realization is in accordance with the work plan, and the use of funds found no deviation or misuse. Thus it can be concluded that budget management in Harjasari Village has fulfilled the accountability aspect.